Calibração de coeficientes de rugosidade em redes reais de abastecimento de água, usando o método iterativo do gradiente hidráulico alternativo - MIGHA - Campos, Rubeny Daniel Garcia (2018)
Computational models have been developed in the last decades, both for the planning and the operation of drinking water supply systems, reaching great advances in relation to their applications. For hydraulic modeling to be reliable and represent reality, it is necessary to calibrate the hydraulic model. The purpose of calibration or what is known as parameter optimization of any model of a physical system is to identify the values ​​of some parameters in the model that are not known a priori. This is achieved by feeding the model with input data and comparing the calculated output variables with the variables measured in the physical system. The calibration of the pipe roughness coefficients, as well as other parameters of the hydraulic models, is a necessary procedure for the reliability of hydraulic simulation results. In this work a computational routine is developed for calibration of the Darcy-Weisbach friction factor followed by the calculation of absolute roughness in real water supply. Also a computational subroutine was developed with the purpose of seeking the best initial roughness value. The study, carried out in a hypothetical network and a real network, also evaluates the performance of the method in situations in which the pressure in all nodes of the network is not known. 10,252 friction factor calibrations were performed to calculate the absolute roughness of the water supply network of the Aldeota, Fortaleza / CE Sector, identifying the areas of low pressure, due to the reduction of the useful diameter of the tube due to the increased roughness, as well as indications of possible leaks in areas with higher pressures. The studies carried out aim to increase the knowledge of the technique, contributing to future studies and improvements in the operation and detection of leaks.